2018
DOI: 10.33182/rr.v3i1.426
|View full text |Cite
|
Sign up to set email alerts
|

Role of Financial Sector Development as a Contingent Factor in the Remittances and Growth Nexus: A Panel Study of Pacific Island Countries

Abstract: Except for emergencies and for technical assistance for raising skills and institution building, foreign aid to Pacific island countries (PICs) for budgetary support has been phased out since the late 1990s. Because of the small sized domestic markets, foreign direct investment (FDI) is small and is confined to development of tourism infrastructure. On the other hand, inward remittances received from the rising number of islanders migrating overseas for work are increasing, far exceeding aid and FDI. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
1
9
2
Order By: Relevance
“…Our finding is supported by Chakraborty and Nunnenkamp 39 and Duan et al 38 who suggest that FDI does not play an essential role in contributing to output growth. However, it is contradictory with the findings of Amri 35 and Jayaraman et al, 53 who claims that FDI and economic growth are positively related. The positive linkage between FDI and economic growth can be explained by both the endogenous and exogenous growth theories.…”
Section: Resultscontrasting
confidence: 56%
“…Our finding is supported by Chakraborty and Nunnenkamp 39 and Duan et al 38 who suggest that FDI does not play an essential role in contributing to output growth. However, it is contradictory with the findings of Amri 35 and Jayaraman et al, 53 who claims that FDI and economic growth are positively related. The positive linkage between FDI and economic growth can be explained by both the endogenous and exogenous growth theories.…”
Section: Resultscontrasting
confidence: 56%
“…The official channels allow transfers to be remitted through the domestic banking system and/or money-transfer organisations whereas the unofficial channels remit mainly in cash or in-kind through the use of carriers such as family members or friends; money or goods taken by the migrant on his/her seasonal visits to his/her home country and; funds remitted through other unlicensed money transfer operators (hawala system). However, transfers through unofficial channels are far more expensive (Jayaraman et al, 2018); it is also higher than the former.…”
Section: Conceptual Review Of Remittances Literaturementioning
confidence: 99%
“…Furthermore, the remittances-financial development conditioning term showed that the two variables act as substitutes. Jayaraman et al (2018) assessed the role of financial sector development in the relationship between remittances and economic growth for a panel dataset of five Pacific Island countries over the period 1997-2014. Through the results of Dynamic Ordinary Least Square (DOLS), the study showed that remittances and financial sector development are substitutes for economic growth.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Financial inclusion further facilitates the all types of foreign inflows either remittances or bonds or portfolio or direct investment. (Alfaro et al, 2004;Jayaraman et al, 2018;Toxopeus & Lensink, 2008). While lack of financial inclusion may lead to continuous income inequality, enhance poverty level, and lower economy growth .…”
Section: Introductionmentioning
confidence: 99%